State Bar of California Annual Meeting at San Diego Town and Country Hotel - Watkins, Howard::::::::: (1989)
Elia Michael Larocca, Judges Brad Hill and Lawrence O'Neill, Sam Palmer, Fresno County Bar Association President G. Dana French, Fresno County Bar Association Vice-President bb, Judge Sandra Snyder and State Bar Board Governor Robert Oliver